Contributions of Two-Component Regulatory Systems, Alternative σ Factors, and Negative Regulators to Listeria monocytogenes Cold Adaptation and Cold Growth - Chan, Yvonne C. (J Food Prot, 2008)
The ability of Listeria monocytogenes to grow at refrigeration temperatures is critical for transmission of this foodborne pathogen. We evaluated the contributions of different transcriptional regulators and two-component regulatory systems to L. monocytogenes cold adaptation and cold growth. L. monocytogenes parent strain 10403S and selected isogenic null mutants in genes encoding four alternative σ factors (sigB, sigH, sigC, and sigL), two regulators of σ(B) (rsbT and rsbV), two negative regulators (ctsR and hrcA), and 15 two-component response regulators were grown in brain heart infusion broth at 4°C with (i) a high-concentration starting inoculum (10(8) CFU/ml), (ii) a low-concentration starting inoculum (10(2) CFU/ml), and (iii) a high-concentration starting inoculum of cold-adapted cells. With a starting inoculum of 10(8) CFU/ml, null mutants in genes encoding selected alternative σ factors (ΔsigH, ΔsigC, and ΔsigL), a negative regulator (ΔctsR), regulators of σ(B) (ΔrsbT and ΔrsbV), and selected two-component response regulators (ΔlisR, Δlmo1172, and Δlmo1060) had significantly reduced growth (P < 0.05) compared with the parent strain after 12 days at 4°C. The growth defect for ΔsigL was limited and was not confirmed by optical density (OD(600)) measurement data. With a starting inoculum of 10(2) CFU/ml and after monitoring growth at 4°C over 84 days, only the ΔctsR strain had a consistent but limited growth defect; the other mutant strains had either no growth defects or limited growth defects apparent at only one or two of the nine sampling points evaluated during the 84-day growth period (ΔsigB, ΔsigC, and Δlmo1172). With a 10(8) CFU/ml starting inoculum of cold-adapted cells, none of the mutant strains that had a growth defect when inoculation was performed with cells pregrown at 37°C had reduced growth as compared with the parent strain after 12 days at 4°C, suggesting a specific defect in the ability of these mutant strains to adapt to 4°C after growth at 37°C. Our data indicate (i) selected σ factors and two-component regulators may contribute to cold adaptation even though two-component regulatory systems, alternative σ factors, and the negative regulators CtsR and HrcA appear have limited contributions to L. monocytogenes growth at 4°C in rich media, and (ii) inoculum concentration and pregrowth conditions affect the L. monocytogenes cold-growth phenotype.